BIG DATA WORLD AND THE NEW MARKETING HORIZONS - Zlateva, Dinka (Revista Inclusiones, 2021)
Marketing has undergone major transformations in the last two decades. Today, people spend most of their time on the Internet. Big data has changed the business landscape beyond recognition, and the marketing industry has been hit hardest by these changes. Technological changes give a wide field for entrepreneurs to operate with ease with a huge amount of data and to make adequately informed decisions. Large information flows allow easier interpretation of consumer behaviour, which opens opportunities to understand better customer needs and the maximum adaptation of product decisions to their requirements. The technological environment has created conditions for marketers to reach their potential. Today, more than ever, highly targeted messages can be sent to the right audience. Customer service is a priority for companies, and this puts companies to the test for systematic market monitoring and adaptation to new technological solutions. The digital age gives an equal start to all companies. Marketers are well aware of the benefits that the digital environment offers, because today, it is not important how big you are in business, but how fast and adaptable to change. The article’s main goal is to present how the digital transformation affects the marketing industry, presenting the benefits provided by the digital environment for business development through the application of innovative marketing solutions for successful positioning. The main aspects of big data and their influence in the marketing industry are systematized. The main research methods in the development are content analysis, the method of analysis and synthesis and the intuitive and systematic approach.